2017
DOI: 10.1016/j.watres.2016.10.068
|View full text |Cite
|
Sign up to set email alerts
|

Impact of external carbon dose on the removal of micropollutants using methanol and ethanol in post-denitrifying Moving Bed Biofilm Reactors

Abstract: Addition of external carbon sources to post-denitrification systems is frequently used in wastewater treatment plants to enhance nitrate removal. However, little is known about the fate of micropollutants in post-denitrification systems and the influence of external carbon dosing on their removal. In this study, we assessed the effects of two different types and availability of commonly used carbon sources -methanol and ethanol- on the removal of micropollutants in biofilm systems. Two laboratory-scale moving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
48
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(64 citation statements)
references
References 64 publications
(104 reference statements)
11
48
2
3
Order By: Relevance
“…The inhibition mechanisms are that methanol will be converted to aldehydes by methanol dehydrogenase, and ethanol will be converted to acetyl coenzyme before being oxidized to acetaldehyde. 79 As noted in previous research, there was no accumulation of NO 2 À in a reactor with added methanol; the contribution rate of anammox denitrication continuously decreased, and the coupling system was seriously inhibited. Peng et al 80 analyzed the methanol in the reactor experimentally; they found that anammox had no activity at 3 to 4 mmol methanol, and the inhibition was irreversible.…”
Section: Organic Inhibitionsupporting
confidence: 53%
“…The inhibition mechanisms are that methanol will be converted to aldehydes by methanol dehydrogenase, and ethanol will be converted to acetyl coenzyme before being oxidized to acetaldehyde. 79 As noted in previous research, there was no accumulation of NO 2 À in a reactor with added methanol; the contribution rate of anammox denitrication continuously decreased, and the coupling system was seriously inhibited. Peng et al 80 analyzed the methanol in the reactor experimentally; they found that anammox had no activity at 3 to 4 mmol methanol, and the inhibition was irreversible.…”
Section: Organic Inhibitionsupporting
confidence: 53%
“…Hence, a number of engineering solutions are being explored to optimize the removal of micropollutants via biological wastewater treatment (Falås et al, 2016;Torresi et al, 2017Torresi et al, , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…As previously discussed, Torresi et al (2017) investigated The influences of cerium dioxide nanoparticles (CeO2 NPs) on nitrogen removal in biofilm were investigated in an SBBR . When testing a progressive concentration of CeO2 NPs addition, the results showed that the removal efficiency could nearly stabilize at 67% with a continuous spike of 10 mg CeO2/L.…”
Section: Moving Bed Biofilm Reactormentioning
confidence: 99%